Time and dose of irrigation impact Tuber melanosporum ectomycorrhiza proliferation and growth of Quercus ilex seedling hosts in young black truffle orchards - Olivera, Antoni; Antonio Bonet, Jose; Oliach, Daniel; Colinas, Carlos (MYCORRHIZA, 2014)
In Mediterranean climate, young truffle-oak orchards are subjected to drought episodes that can compromise the development of Tuber melanosporum. We investigated the responses of T. melanosporum to water supply in three periods: May to July, August to October, and May to October. In each period, five water doses were established: 0, 25, 50, 75, and 100 % of the reference evapotranspiration (ETo). Five orchards were planted with Quercus ilex inoculated with T. melanosporum, and in each orchard, we arranged a two-factorial design with irrigation period and irrigation dose as main factors to test their combined effects on the development of both T. melanosporum and Q. ilex after 3 years in the field. Irrigation period significantly interacted with irrigation doses for the absolute presence per seedling of T. melanosporum mycorrhizae. Irrigation in May-July increased significantly T. melanosporum colonization in seedlings irrigated with 50 % ETo dose compared to the 0 % ETo dose. A similar pattern with smaller differences in means was observed in August-October period, but the irrigation doses did not change T. melanosporum colonization when we watered from May to October. We found ectomycorrhizae different from T. melanosporum in 51 % of the seedlings studied, but their presence was marginal. Our results suggest that a moderate irrigation dose promotes seedling growth and number of fine root tips per unit of fine root length, which may be potentially colonized by T. melanosporum.
Keywords: Black truffle; Ectomycorrhizae; Evapotranspiration; Preproduction; Quercus ilex